2015
DOI: 10.1016/j.atherosclerosis.2015.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Carotid atherosclerosis and cardiovascular health metrics in old subjects from the AGES-Reykjavik study

Abstract: Background Ideal cardiovascular (CV) health by simultaneous presence of 7 ideal health metrics (blood pressure, cholesterol, glucose, smoking, BMI, physical activity and diet) has been defined by the American Heart Association. In the current study we investigated the association of a CV health score (range 0–14), on the extent and progression of carotid atherosclerosis, assessed as carotid intima-media thickness (cIMT) and total plaque area (TPA) by ultrasound at 5 years interval. Methods and Results A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
15
1
Order By: Relevance
“…The ultrasound protocol of the CIMT is described in more detail elsewhere (9,10). In brief, images of the right and left carotid artery (CCA), bifurcation, and internal carotid artery (ICA) were acquired with an Acuson Sequoia C256 with a two-dimensional 8 MHz linear array transducer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrasound protocol of the CIMT is described in more detail elsewhere (9,10). In brief, images of the right and left carotid artery (CCA), bifurcation, and internal carotid artery (ICA) were acquired with an Acuson Sequoia C256 with a two-dimensional 8 MHz linear array transducer.…”
Section: Methodsmentioning
confidence: 99%
“…Calcium was quantified by Agatston scores of coronary arteries, proximal aortic arch and distal aorta using computerized tomography (CT) images of the chest (10,11,12) Cerebral infarction: The scoring of cerebral infarcts has been described in detail elsewhere (13,14). In brief, infarcts were scored by trained radiographers and defined as defects of the brain parenchyma with a signal intensity isointense to cerebrospinal fluid on all MR images (FLAIR, PD/T2-weighted images), associated hyperintensity on T2-weighted and FLAIR images with a minimal diameter of 4 mm, except for infarcts in the cerebellum and brain stem which had no size criteria and did not require associated hyperintensity.…”
Section: Methodsmentioning
confidence: 99%
“…This same study is the sole, to date, that has addressed the association between ideal CVH and carotid plaques. 30 In this prior study, an inverse-graded association was reported between higher CVH score and total plaque area but only in men. We have extended these results using a much larger sample size and by reporting significant associations between CVH and carotid plaques in both sex.…”
Section: Ideal Cvh and Carotid Structurementioning
confidence: 99%
“…[28][29][30][31] Lower CCA-IMT has also been associated with the number of ideal CVH metrics among adolescents 26 and among young adults in the United States, Finland, and Australia. 30 To the best of our knowledge, only 2 previous studies have specifically examined the association of CVH with CCA-IMT among adults. In the first study conducted in twins, ideal CVH was inversely associated with CCA-IMT, independently of shared genetic and familial factors.…”
Section: Ideal Cvh and Carotid Structurementioning
confidence: 99%
See 1 more Smart Citation